PENGARUH PERUBAHAN HARGA EMAS DUNIA TERHADAP NILAI TUKAR RUPIAH - Yulida Putri; Doni Satria; Fakhruddin Fakhruddin (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2022)
The objectives of this research are to decide the effect of: (1) modifications in world gold expenses on the rupiah exchange charge; (2) The difference among Indonesian and American hobby fees against the rupiah trade fee; (3) The difference between Indonesia and the usa's inflation towards the rupiah trade charge; (4) net exports against the rupiah alternate rate. the use of month-to-month time collection data from 2004-2019. Inductive analysis on this look at includes: (1) desk bound test; (2) more than one linear regression analysis; (three) Multicolonearity check; (four) Heteroscedasticity take a look at; (five) Normality take a look at (6) Autocorrelation check (7) Determinant coefficient (eight) T check (nine) F take a look at.The results of the study suggest that: (1) there is a great poor impact of worldwide gold costs at the rupiah alternate charge; (2) there may be a poor and insignificant impact of the distinction between Indonesian and American interest prices on the rupiah change price; (three) there may be a fine and vast effect of the inflation difference among Indonesia and america at the trade price; (4) there's a poor and great effect of net exports at the rupiah exchange price.primarily based at the research results, it's far cautioned to government policy makers to pay attention to this studies variable to be able to hold the stability of the rupiah exchange fee.